2021
DOI: 10.1016/j.mayocp.2021.03.039
|View full text |Cite
|
Sign up to set email alerts
|

How Feedback Is Given Matters: A Cross-Sectional Survey of Patient Satisfaction Feedback Delivery and Physician Well-being

Abstract: Objective: To evaluate how variation in the way patient satisfaction feedback is delivered relates to physician well-being and perceptions of its impact on patient care, job satisfaction, and clinical decision making. Participants and Methods: A cross-sectional electronic survey was sent to faculty physicians from a large academic medical center in March 29, 2019. Physicians reported their exposure to feedback (timing, performance relative to peers, or channel) and related perceptions. The Professional Fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Seventy percent of dermatologists agreed that PRs add an element of stress to work and most agreed that PRs contribute to their negativism/cynicism about the workplace. Our findings are similar to a study from 2017 which found that the majority of physicians believed PRs increase physicians' job stress 32 . Females, compared to males, reported higher perceived stress because of PRs; this finding echoed prior data indicating higher levels of burnout in female physicians 33 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Seventy percent of dermatologists agreed that PRs add an element of stress to work and most agreed that PRs contribute to their negativism/cynicism about the workplace. Our findings are similar to a study from 2017 which found that the majority of physicians believed PRs increase physicians' job stress 32 . Females, compared to males, reported higher perceived stress because of PRs; this finding echoed prior data indicating higher levels of burnout in female physicians 33 .…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to a study from 2017 which found that the majority of physicians believed PRs increase physicians' job stress. 32 Females, compared to males, reported higher perceived stress because of PRs; this finding echoed prior data indicating higher levels of burnout in female physicians. 33 A study from 2019 found that young, female physicians tend to receive lower patient scores compared to males, which, in conjunction with experiencing higher perceived stress, may pose additional barriers to success.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, there is some evidence that providing patient feedback to physicians can improve measures of professional fulfillment. 25 Future research could identify aspects of resident care that are identified as being most important to patients themselves, such as wanting to know the care team and being more actively involved in teaching. 26 Qualitative studies could inform the development or modification of any patient-derived assessment instruments to ensure patient values and preferences are well represented.…”
Section: Discussionmentioning
confidence: 99%
“…Because patient satisfaction with surgical resident care is generally high, providing this positive feedback to surgical residents could be beneficial in restoring a sense of meaning and purpose to their rigorous training. In fact, there is some evidence that providing patient feedback to physicians can improve measures of professional fulfillment 25…”
Section: Discussionmentioning
confidence: 99%
“…Despite substantial literature on the elements of feedback necessary to promote behavior change, there is limited research specifically exploring feedback-related behaviors by leadership that can promote feedback acceptability and incorporation. 13 15 There is also limited research on the role of feedback provision and well-being, with some suggestion that feedback from supervisors can promote well-being of those they supervise if it is done well. 16 18 For instance, leaders who provide task performance feedback have lower rates of absenteeism due to illness.…”
mentioning
confidence: 99%